An Analysis of The Use of ICT Tools and Its Problems in Teaching and Learning Process at SMA Negeri 2 Semarapura - N.K Swandewi (Journal of Psychology and Instruction, 2018)
This study aimed at investigating (1) types of ICT tools implemented in teaching and learning process (2) English teacher’ planning of the use of ICT tools in lesson planning (3) procedures implemented in teaching English using the ICT tools (4) the problems faced by English teachers who used ICT tools in teaching and learning process at SMA Negeri 2 Semarapura when using ICT tools in teaching and learning process. This study was descriptive qualitative research involving three English teachers of SMA Negeri 2 Semarapura. The instruments used for data collection were researcher, questionnaire, interview guide, teachers’ lesson plan, observation sheet, and recorder. The methods of data collection were survey, interview, lesson plan analysis, observation, and recording. The result of the study showed that English teachers of SMA Negeri 2 Semarapura had already implemented ICT tools in teaching and learning process. Types of ICT tools used were laptop, LCD projector, speaker, video, Power Point, internet, and e-learning namely Quipper School. Before implementing those types of ICT tools, teachers planned ICT tools in the lesson planning. The use of ICT tools were planned explicitely in teaching media and tools as well as learning resources, while implicitely in steps of teaching and learning activity. In implementing ICT tools, the teachers had their own procedures which depended on types of ICT tools used and topic taught. Teachers encountered four main problems namely infrastructural problems, technical problems, problem of time, and lack of teachers’ competence in using ICT tools.